Indonesian English Teacher’s Stories in Designing Differentiated Speaking Activity Instruction: A Narrative Study - Maulana, Azriel; Asrimawati, Inayati Fitriyah; Febriyanti, Emma Rosana (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This inquiry aimed to explore and make sense of the stories of an English language teacher’s experiences using the CEFR framework to design the DI of speaking activity instruction. More specifically, the research was intended to understand the usage of CEFR in designing differentiated learning of speaking activity instruction. To achieve the purpose of the research, a narrative inquiry is employed. One English language teacher at a junior high school in Indonesia participated in this research and shared her experience using CEFR as a tool for designing differentiated learning. The data were collected through the online interview to collect information from the teacher's Zoom application and analyzed qualitatively in steps. The findings showed that in narrative research, limited attention has been paid to how English teachers constructed their differentiated teaching-speaking instruction through a CEFR framework. this narrative inquiry indicated that CEFR accommodated students’ needs and fostered students’ competencies, effectively designing differentiated teaching and speaking instruction. English teachers had different stories in constructing differentiated instruction (DI) tailored to different learner needs within the CEFR framework.